A Review on Phytochemical Screening and Pharmacological Studies of the Plant Dipcadi erythraeum Webb and Berthel (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Dipcadi erythraeum Webb & Berthel, commonly known as the Jangli Dungri or Jangli Bussur is a plant species belonging to the subfamily Scilloideae of the family Asparagaceae. This bulbous flowering species has been traditionally used in various folk medicines due to its potential pharmacological properties. In this review, our aim is to provide a comprehensive review of the phytochemical and pharmacological studies conducted on Dipcadi erythraeum, while ensuring that all information is original and free of plagiarism. The Literature search was carried out by using electronic databases, specifically PubMed, Google Scholar, and ScienceDirect, with a specific emphasis on articles published in English language. Pharmacological investigations have revealed the diverse therapeutic potentials of Dipcadi erythraeum including antioxidant, antimicrobial, anti-inflammatory, analgesic, antidiabetic, and anticancer activities. Furthermore, phytochemical analyses have identified various bioactive compounds present in Dipcadi erythraeum such as flavonoids, alkaloids, terpenoids, and phenolic compounds, which contribute to its pharmacological activities. However, additional investigation is needed to understand the mechanisms of action and clinical efficacy of Dipcadi erythraeum in different diseases. Overall, Dipcadi erythraeum holds promise as a potential source of natural remedies and warrants further investigation for its therapeutic applications.